tell me where i m doing wrong and what should be the correct answer that i m not getting L. H. S = RHS
Attachments:
![](https://hi-static.z-dn.net/files/d11/64e17cf35fec3190351d0f9f9ffd3402.jpg)
Answers
Answered by
5
To prove that a-1 /a-1 +b-1 +a-1 /a-1 -b-1 = 2b2 /b2 -a2Lets take the LHS (Left Hand Side) first:
=1/a÷1/a+1/b + 1/a÷1/a -1/b
Next take the LCM for the denominator, so it becomes:
=1/a÷b+a /ab + 1/a÷b-a /ab
=1/a×ab /b+a+ 1/a×ab /b-a
Now 'a' gets cancelled in both the numerator and the denominator. So it becomes:
=1/a×ab /b+a+ 1/a×ab /b-a
=b /b+a+b /b-a
take the LCM of the denominator and so it becomes:
=b(b-a)/(b+a)(b-a)+b(b+a)/(b-a)(b+a)
=b2 -ab /b2 -a2 +b2 +ab /b2 -a2
=b2 -ab +b2 +ab /b2 -a2
=b2+b2/b2-a2
=2b2/b2 -a2 ==== RHS (Right Hand Side)
hope it helps u!!!!!
=1/a÷1/a+1/b + 1/a÷1/a -1/b
Next take the LCM for the denominator, so it becomes:
=1/a÷b+a /ab + 1/a÷b-a /ab
=1/a×ab /b+a+ 1/a×ab /b-a
Now 'a' gets cancelled in both the numerator and the denominator. So it becomes:
=1/a×ab /b+a+ 1/a×ab /b-a
=b /b+a+b /b-a
take the LCM of the denominator and so it becomes:
=b(b-a)/(b+a)(b-a)+b(b+a)/(b-a)(b+a)
=b2 -ab /b2 -a2 +b2 +ab /b2 -a2
=b2 -ab +b2 +ab /b2 -a2
=b2+b2/b2-a2
=2b2/b2 -a2 ==== RHS (Right Hand Side)
hope it helps u!!!!!
Answered by
2
Hey !
✴Check the above attachment !
and check where u went wrong ^ _ ^
________
☺☺
✴Check the above attachment !
and check where u went wrong ^ _ ^
________
☺☺
Attachments:
![](https://hi-static.z-dn.net/files/d12/e1d1d151f78ec2e0198c6e62889aba41.jpg)
Anonymous:
:)
Similar questions